Paving the way into virtual reality - a transition in five stages - Sproll, Daniel; Freiberg, Jacob; Grechkin, Timofey; Riecke, Bernhard E. (2013)
Many of today's virtual reality (VR) setups are very much focused on technical aspects rather then the benefits of a coherent user experience. This work explores the idea of enhancing the VR experience with a transition phase. On a physical level, this transition offers the user a meaningful metaphor for entering a new world, mimicking a real physical translation from one place to an- other. On a mental level, it captures the user's attention and evokes anticipation and involvement with the final goal of engaging the user's mind in active co-creation of the experience. We present a conceptual model of a 5-stage transition and describe an implementation we are currently developing, including possible evaluation procedures.
Keywords: Riecke; Riecke_2013; TransLocation; Virtual reality (VR); bernhard-riecke; conferencePapers; daniel-sproll; jake-freiberg; poster; timofey-grechkin; transition; transition2VR